Towards superior high temperature properties in low density ferritic AlCrFeNiTi compositionally complex alloys. (1st September 2021) - Wolff-Goodrich, Silas; Haas, Sebastian; Glatzel, Uwe; Liebscher, Christian H.
Graphical abstract: Abstract: Three novel precipitation strengthened bcc alloys which exhibit a smooth microstructural gradient with composition have been fabricated in bulk form by induction casting. All three alloys are comprised of a mixture of disordered A2-(Fe, Cr) and L2 1 -ordered (Ni, Fe) 2 AlTi type phases both as-cast and after long-term annealing at 900 ∘ C. The ratio of disordered to ordered phase, primary dendrite fraction, and overall microstructural coarseness all decrease as Cr is replaced by Al and Ti. Differences in phase composition are quantified through domain averaged principal component analysis of energy dispersive spectroscopy data obtained during scanning transmission electron microscopy. Bulk tensile testing reveals retained strengths of nearly 250 MPa up to 900 ∘ C for the alloys which contain a nanoscale maze-like arrangement of ordered and disordered phases. One alloy, containing a duplex microstructure with ductile dendritic regions and highly creep resistant interdendritic regions, shows a promising balance between high temperature ductility and strength. For this alloy, tension creep testing was carried out at 700, 750, and 800 ∘ C for a broad range of loading conditions and revealed upper bound creep rates which surpass similar ferritic superalloys and rival those of several conventionally employed high temperature structural alloys, including Inconel 617 and 718, at much lower density and raw material cost.